Where are the largest livestock and cocoa emissions generated in Caquetá, Colombia? - Yomayuza Herrera, Karoll Valentina (2024)
A study conducted in the department of Caquetá, Colombia, by the Low-Emission Food Systems team of the Allinace Bioversity-CIAT as part of the CGIAR AgriLAC Resilient Initiative, identified the production stages that generate the highest emissions in the livestock and cocoa chains in the department. The research proposes solutions to mitigate their impact and is key to understanding how Colombia can meet its climate commitments and move towards a more sustainable and resilient agriculture.